Body Mass Index to Age Ratio: A Cost Effective Implant Selection Guideline for Total Hip Arthroplasty - Bolz, Nicholas; Odeh, Khalid; Osmani, Feroz; Bearison, Craig; Schwarzkopf, Ran; Iorio, Richard (The Journal of Hip Surgery, 2019)
The incidence of total hip arthroplasty (THA) is dramatically increasing, placing a financial burden on the health care system as a whole. These economic challenges have inspired innovation in health care and spurred the implementation of value-based-care models. In this new health care environment, it is imperative to develop strategies that reduce cost while maintaining quality. The authors developed an implant selection guideline system for THA based upon a ratio of patient body mass index (BMI) to age. Patients are divided into either a high, medium, or standard demand category based on a BMI/age ratio of > 0.60, 0.60–0.41, and < 0.40, respectively. Retrospectively, the authors reviewed surgical reports of 1,990 patients who underwent primary THA at their institution from January 2012 to March 2014 to identify the type of implants utilized and analyze the potential cost impact of implementing this standardization system into clinical practice. Of 701 standard demand patients, 31.2% received higher cost implants than their demand necessitates under their model. A 16.5% of the 892 medium demand patients received high demand implants. High and medium demand implants cost 21.1 and 10.5% more than standard demand, respectively. Collectively, application of the BMI/age ratio would have resulted in a 2.2% reduction in overall THA implant cost and 15% if high demand implants had been used in every patient. Implementation of a BMI/age ratio for THA implant selection will reduce costs. This strategy may allow hospitals to more accurately predict and control future costs which is of growing importance in today's bundled payment and value-based-care environment.
Keywords: total hip arthroplasty; bundled payments; implant selection; value-based care; demand matching